Analysis of waste handling strategies for riverbanks communities - Syafari, Muhammad Riduansyah; Ridwan, M. Nur Iman; Sugiannor, Sugiannor; Shaddiq, Syahrial (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Waste management is essential to protecting the environment and minimizing its negative impact on human health and the ecosystem. The low participation of riverbank residents in maintaining and creating a clean environment in the river and its surroundings has prompted the Environmental Service to create a program called